Pengaruh Kedisplinan Guru Terhadap Hasil Belajar Siswa Kelas V SD YPPGI Guopaka, Distrik Tiom, Kab. Lanny Jaya Papua - Juarni Gea; Efvi Noyita (Sekolah Tinggi Teologi Real Batam, 2020)
The teacher's role is key to the functioning of a school education institution. Teachers have enormous responsibility in an effort to deliver their students to the educational goals they aspire to. In this case the teacher is responsible for meeting the needs of his students, both spiritual, moral, aesthetic, and physical needs of each student. Therefore, a teacher must be able to behave properly and well in every way, especially in terms of discipline. Discipline is one very important aspect of the learning process. Without discipline, the predetermined learning targets cannot be achieved optimally. This study aims to determine whether there is an effect of teacher discipline on learning outcomes at SD YPPGI Guopaka, Tiom district, Lanny Jaya Papua district. In this study the authors used data analysis techniques with data processing using the SPSS (Statistical Package for Social Science) program with the hope that all the data that has been obtained has met the requirements to conclude the results of a study. The results of the research conducted stated,